The Plastic Bag Regulations For A Sustainable Environment - Nar, Mehmet (International Journal of Contemporary Economics and Administrative Sciences, 2019)
Global problems, which are among the most serious matters of our age, threaten the existence of the world and humanity. The most basic concept we face regarding the aforementioned problems is the concept of sustainability. This matter becomes even more important especially considering the use of plastic bags. This study, which summarizes the most recent state of sustainable development, focuses on environmental sustainability and plastic bag consumption. Afterwards, the negative effects of plastic bag use on environment and health are evaluated. In this context, the effects of the taxation arrangements and pricing policies implemented towards plastic bag use for the sake of creating a sustainable environment were analyzed.